Project-based learning – A significant learning at Júlia Kubitschek state college - Madeira , Fabiana Ferreira Braga; Teixeira , Gerlinde Agate Platais Brasil (Seven Editora, 2023)
The project entitled Project-based learning was developed at Colégio Estadual Júlia Kubitscheck and was inspired by the period of the COVID-19 pandemic in a hybrid teaching format. The classes taught had a remote profile, sometimes they were carried out by video call communication service, sometimes by recorded classes, and made available on the SEEDUC/RJ platform. Faced with this reality, active methodologies enable the construction of collaborative classes based on more lively and meaningful learning experiences for students. The objective of the project was to highlight the themes of inclusive education - deafness, physical disability, autism spectrum disorder, intellectual disability, blindness, high abilities, and giftedness through an active methodology that awakens youth protagonism related to the programmatic contents of Portuguese Language, when possible and that the contents of the Portuguese Language curricular component were discussed in the projects. As a theoretical basis for the development of the project, it was based on Bacich (2017) who designs models of active methodologies for innovative practices in the classroom. The work methodology used was TBL Team-based learning – learning in teams that offer a participatory teaching model, as students can do it together, share ideas, and collaborate (AMARAL, 2017). The results indicate that it is possible in a public education system to offer innovative educational models to students, according to the national curriculum base, and that integrate them into the new literacies resulting from a contemporary society that consumes new technologies. The students resignified their knowledge, and their learning, they felt part of the teaching process. DOI:https://doi.org/10.56238/devopinterscie-200